Student Reception of English Learning through Animated Videos in Sidoarjo Elementary Schools: Respon Siswa terhadap Pembelajaran Bahasa Inggris Menggunakan Video Animasi di Sekolah Dasar di Sidoarjo - Areta Daffara Prameswari; Yuli Astutik (Academia Open, 2023)
This study aims to determine how students respond in learning English using animated videos in grade I SD PLUS FATIMAH AZ – ZAHRO' Sidoarjo. This research is a qualitative research in which the data is taken from the analysis of direct observation and interviews with English class teachers. Collecting data in this study using documentation and interviews. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results of this study indicate that student responses are divided into three components, namely cognitive, affective, and conative. This study also shows that students in one class are divided into three parts in the ability to understand English learning, namely the competent level, medium level, and low level. Lack of interest in learning English and internal and external factors such as family background and students' skills or abilities are one of the causes of students' lack of response to learning English. Highlights: The study focuses on understanding student responses in learning English using animated videos in a specific grade and school in Sidoarjo. The research employs qualitative methods, gathering data through direct observation, interviews with English teachers, and documentation. The study identifies three components of student responses: cognitive, affective, and conative, and highlights the varying levels of English understanding among students. The lack of interest and external/internal factors also affect students' response to English learning. Keywords: English learning, Animated videos, Student responses, Grade I, SD PLUS FATIMAH AZ – ZAHRO' Sidoarjo